Enhancing Workspace Ergonomics to Mitigate Musculoskeletal Disorders in Stamped Batik Production (Case Study at PT.XYZ) - Fitriyah, Ita; Hutabarat, Julianus; Vitasari, Prima (LPPM Universitas Andalas, 2024)
Batik is one of the works owned by the Indonesian Nation, which has noble values and is recognized by other nations. The rapid development of batik makes batik makers need to pay attention to the production process carried out, In carrying out the activities of making stamped batik, it has not been supported by a special work table. Still using an ordinary stamp table that is less comfortable to use for stamped batik. So that in doing their work craftsmen have low productivity and efficiency. This research was conducted at PT XYZ to evaluate and reduce the risk of musculoskeletal disorders in stamped batik makers through ergonomic work table redesign. The research method used is case study-based quantitative, with a population of PT XYZ employees who work as stamped batik makers. Primary data was collected through observation, questionnaires and interviews. Posture measurements were carried out using the NBM (Nordic Body Map) questionnaire, to determine musculoskeletal complaints including 28 muscle parts in the musculoskeletal system on both sides of the body right and left. Then posture measurements were taken using the REBA (Rapid Entire Body Assesment) method. The results of the NBM questionnaire showed that before the improvement of the stamp batik had a high chart of complaints of pain in the musculoskeletal muscles and also the results of the REBA score showed a high risk of musculoskeletal disorders, especially in the neck, shoulders, bronze, arms and legs. After the implementation of a more comfortable stamp work table design and stamp stove table (Adjustable) there was a significant decrease in the REBA score decreasing from 8 to 1. This shows a significant reduction in the risk of musculoskeletal disorders, so that ergonomic work table design can reduce the risk of musculoskeletal disorders at PT XYZ and increase worker comfort.